Norms regarding secondary victimization of bullying victims: Do they differ according to the victim's categorization? - Correia, I. (2010)
Two studies with a 2 valence of the image (positive, negative) x 2 victim's category (ingroup; outgroup) between-subjects design, investigated the existence of prescriptive norms regarding secondary victimization of bullying victims as well as the influence of the categorization of the victim on those same prescriptive norms among 7th graders. Study 1 addressed a scenario of physical bullying. Study 2 addressed a scenario of verbal bullying combined with social exclusion. Results showed that norms prescribe that the ingroup victim of physical bullying should be the least secondarily victimized. Furthermore it was found that for both types of bullying a positive image can be conveyed by secondarily victimizing more an outgroup victim than an ingroup victim.